Differential Diagnosis of Crohn’s Disease and Ulcerative Primary Intestinal Lymphoma: A Scoring Model Based on a Multicenter Study - Yang, Hong; Zhang, Huimin; Liu, Wei; Tan, Bei; Guo, Tao; Gao, Xiang; Feng, Rui; Wu, Kaichun; Cao, Qian; Ran, Zhihua; Liu, Zhanju; Hu, Naizhong; et al. (Frontiers in Oncology, 2022)
Background: Differential diagnosis of Crohn’s disease (CD) and ulcerative primary intestinal lymphoma (UPIL) is a tough problem in clinical practice. Aims: The aim of our study was to identify key differences between CD and UPIL patients and to further establish a scoring model for differential diagnosis. Methods: A total of 91 CD and 50 UPIL patients from 9 tertiary inflammatory bowel disease centers were included. Univariate and multivariate analyses were used to determine significant markers for differentiating CD and UPIL. A differential scoring model was established by a logistic regression analysis. Results: The differential model was based on clinical symptoms, endoscopic and imaging features that were assigned different scores: intestinal bleeding (-2 points), extraintestinal manifestation (2 points), segmental lesions (1 point), cobblestone sign (2 points), homogeneous enhancement (-1 point), mild enhancement (-1 point), engorged vasa recta (1 point). A total score greater than or equal to 1 point indicates CD, otherwise UPIL was indicated. This model produced an accuracy of 83.66% and an area under the ROC curve of 0.947. The area under the ROC curve for validation using the 10-fold validation method was 0.901. Conclusion: This study provided a convenient and useful model to differentiate CD from UPIL.